Stage one Norwood procedure in an emerging economy:Initial experience in a single center - Rakhi Balachandran; Suresh G Nair; Sunil S Gopalraj; Balu Vaidyanathan; Brijesh P Kottayil; Raman Krishna Kumar (Wolters Kluwer Medknow Publications, 2013)
Objective: The evolution of surgical skills and advances in pediatric cardiac intensive care has resulted in Norwood procedure being increasingly performed in emerging economies. We reviewed the feasibility and logistics of performing stage one Norwood operation in a limited-resource environment based on a retrospective analysis of patients who underwent this procedure in our institution. Methods : Retrospective review of medical records of seven neonates who underwent Norwood procedure at our institute from October 2010 to August 2012. Results: The median age at surgery was 9 days (range 5-16 days). All cases were done under deep hypothermic cardiopulmonary bypass and selective antegrade cerebral perfusion. The median cardiopulmonary bypass (CPB) time was 240 min (range 193-439 min) and aortic cross-clamp time was 130 min (range 99-159 min). A modified Blalock-Taussig (BT) shunt was used to provide pulmonary blood flow in all cases. There were two deaths, one in the early postoperative period. The median duration of mechanical ventilation was 117 h (range 71-243 h) and the median intensive care unit (ICU) stay was 12 days (range 5-16 days). Median hospital stay was 30.5 days (range 10-36 days). Blood stream sepsis was reported in four patients. Two patients had preoperative sepsis. One patient required laparotomy for intestinal obstruction. Conclusions:Stage one Norwood is feasible in a limited-resource environment if supported by a dedicated postoperative intensive care and protocolized nursing management. Preoperative optimization and prevention of infections are major challenges in addition to preventing early circulatory collapse.